1003-й свободный человек - Антоничева Марта Юрьевна (Эксмо, 2021)
Экземпляры: Камская библиотека (20220523) / Инвентарный номер: 12871 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 72 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6